Giant popliteal aneurysm with deep vein thrombosis, foot drop and arteriomegali - Goncu, Tugrul (BMJ Publishing Group, 2009)
Popliteal artery aneurysms are the most common peripheral arterial aneurysms and are the second most common aneurysm after abdominal aortic aneurysms. Popliteal artery aneurysm affects mostly elderly men and atherosclerosis plays the major role in the aetiology of the disease. The management of popliteal artery aneurysms requires great care. Popliteal aneurysms are asymptomatic or otherwise present with intermittent claudication, compression symptoms in the popliteal fossa, distal embolisation and, rarely, rupture. We present a patient with a remarkably large popliteal aneurysm of 8×11 cm presenting as a popliteal swelling with foot drop and deep vein thrombosis and limb ischaemia. According to our thorough search of literature printed in English, it is one of the largest reported popliteal aneurysms with arteriomegaly, and its co-existing symptoms are unusual. The diagnostic investigations and treatment are presented.